Radiation Techniques for Recti Carcinoma at the Cancer Center Radiotherapy Santosa Hospital Bandung Kopo - Suswanto; Arif, Muhammad (Jurnal Ilmu Kesehatan (JIKSAN), 2025)
This study aimed to determine the radiotherapy irradiation technique in recti carcinoma. This research method is descriptive qualitative, in which the author describes in detail the facts regarding Standard Operating Procedures (SOP) for irradiation techniques for recti carcinoma at the Santosa Hospital Bandung Kopo Cancer Center. Based on research at Santosa Hospital Bandung Kopo, the results were obtained: irradiation technique using the Linac plane, 3D CRT (Conformal Radiation Therapy) technique in the irradiation direction of 2700, 3300, 300, 900, 1200 and 1800 in 25 fractions.